The Methodological Framework of Feasibility Study to Support Strategic Planning. (10th June 2016) - Bonifaci, Pietro; Copiello, Sergio; Stanghellini, Stefano
Abstract: During the last decades, strategic planning has spread across Italy so that, nowadays, a quite large number of cities have their own plan. This paper aims to provide an insight into the role of the financial evaluation in supporting strategic planning, under the methodological framework of the Feasibility Study. By discussing the case study of the Strategic Plan of Palermo, the paper highlights strengths and weaknesses of action projects and their dependence both on exogenous and endogenous factors. The paper concludes by stressing the role of financial evaluation as a means to identify weaknesses able to affect the project implementation, as well as to highlight the conditions to be exploited in order to improve the success probability for strategic projects.